158 Cognitive, Functional and Psychosocial Outcome After Severe Traumatic Brain Injury: A Cross-Sectional Study at a Tertiary Care Trauma Center. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Sinha, Sumit; Nehra, Ashima; Sharma, Bhawani S.
Abstract: INTRODUCTION: Traumatic brain injury (TBI) constitutes a significant public health problem worldwide. The aim of the study was to assess cognitive, functional and psychosocial outcome in patients with severe traumatic brain injury. METHODS: A total of 77 survivors of severe TBI treated at our center were prospectively assessed on outdoor basis 1 year after injury. These patients were assessed for cognitive, functional and psychosocial outcome using cognitive outcome tests, Dysfunctional Analysis Questionnaire and Personality Trait Inventory, respectively. Cognitive and functional outcome was assessed as average and above average recovery (good recovery) or below average recovery (poor recovery). Psychosocial outcome was assessed as average recovery (good recovery) or mild impairment and severe impairment (poor to very poor recovery). Statistical analysis was done using χ 2 and Fisher exact tests. RESULTS: The ability to learn new things was the most affected aspect of cognitive function and only 1% of patients had good recovery in this domain. However, 44% had good outcome for simple memory. Many patients (61%) showed good recovery in several aspects of functional status. At the end of 1 year, 62.5% of patients still remained unemployed. Additionally, 45.4% of patients had good recovery, while 37% had severe impairment for various personality traits assessing the psychosocial outcome. Impaired emotional stability impacted 40% of patients, while 57% of patients showed impaired recovery in depressive tendency. CONCLUSION: At 1-year follow-up, 61% of patients had good recovery in functional outcome and 45.4% in psychosocial outcome after severe TBI. However, improvement in cognitive outcome was not so optimistic, with the ability to learn new things being the most affected domain.